NAS ONDAS DO RÁDIO – UM OBJETO DE APRENDIZAGEM DIGITAL PARA O ENSINO MÉDIO - Hammarstron, Adriane W.; Zarth, Antônio M. F.; Lindorfer, Carine; Pereira, Juliane S.; Pereira, Tânia M.; Ammar, Marwan; Alcântara, Romário L. (Salão do Conhecimento, 2013)
Resumo